Distribuições dos nervos fibular comum e tibial na coxa e perna em tamanduás-bandeira (Myrmecophaga tridactyla - Linnaeus, 1758) e descrição anatômica de pontos para bloqueios anestésicos - Gomes, Andréa Regina Abrantes (2013)
We analyzed the distribution of the nervus fibularis communis and tibialis in three giant anteaters (Myrmecophaga tridactyla) from the collection of Animal Anatomy Laboratories at Universidade Federal de Uberlândia and Universidade Federal de Goiás, which were injected and preserved in an aqueous solution of 10% formaldehyde. It was noted that those nerves derive from the ischiadicus, and the fibularis communis divided into nervus fibularis profundus and superficialis, distributing to the musculis abductor cruris caudalis, biceps femoris, extensor digitorum lateralis, longus and brevis, fibularis longus and brevis, and tibialis cranialis; The nervus tibialis innerved the musculis flexor digitorum superficialis and profundi, gastrocnemius and popliteus. Drawing an imadinary line in the mid-lateral region of the tuberositatis tibia, the nervus fibularis communis may be blocked in its proximal portion, the caudal third, between the tendon of insertion of the biceps femoris and lateral side of musculus gastrocnemius (middle third); and on the lateral side of the tibiotarsal joint, between the tendons of insertion of the musculi extensor digitorum lateralis and longus. Considering another imaginary line on the medial side of the leg, originating in the caudal region of the condylus medialis tibia, the nervus tibialis may be blocked in its proximal third, between the lateral and medial portions of the musculus gastrocnemius, and distally, between the tuber calcanei and the tibia caudodistal face.